(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examined the socio-economic factors influencing child labour in Nigeria. The instruments for data collection were the questionnaire and the in-depth interview schedules. The sample size used for the study was 621 (615 for the quantitative distribution and 6 for the IDIs). The quantitative data gathered were analysed with Statistical Package for the Social Sciences using percentages (%) and Chi-square (χ2) statistics was used to test the three hypotheses, while the qualitative data gathered was analysed in themes as complement to the quantitative data. The study found that religious sex (χ2 = (615), .081; df = 1, pے =.776), education (χ2 = (N615), 2.024; df = 1, pے =.155) and marital status (χ2 = (N=615), .055; df = 1, pے =.815) had no statistically significant relationship with the effect of child labour practice while only age (χ2= (N=615), 14.577; df=1, pے =.000) had a statistical significant relationship. Furthermore, sex (χ2 = (N=615), .678; df = 1, pے =.410), marital status (χ2 = (N= 615), .012; df = 1, pے =.911), religious affiliation (χ2 = (N=615), .003; df = 1, pے =.957), education (χ2 = (N= 615), .310; df = 1, pے =.578) and occupation (χ2 = (N=615), .849; df = 1, pے =.357) showed no statistically significant relationship with the influence of child labour practices. Three hypotheses were tested and they were all accepted. Results from the regression analysis showed that only marital status had the most positive influence on child labour pratices. Results from the study has shown that child labour practices have negative effect on the child, thus, there is the need to eradicate all forms of child labour through championing sensitization and enlightenment programmes. Also, people who still choose to engage children in child labour after these sensitization and enlightenment programmes should be severely punished by the law to deter others from engaging in such acts. Finally, the study revealed that, government, youth corps members, community leaders and the general public have a role to play in putting an end to the socio-economic factors influencing child labour practices in Nigeria.